2004
DOI: 10.1074/jbc.m409105200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Domain II in Toxicity of Anthrax Lethal Factor

Abstract: Anthrax lethal factor (LF) is a Zn2؉ -metalloprotease that cleaves and inactivates mitogen-activated protein kinase kinases (MEKs). We have used site-directed mutagenesis to identify a cluster of residues in domain II of LF that lie outside the active site and are required for cellular proteolytic activity toward MEKs. Alanine substituted for Leu 293 514 and Asn 516 resulted in toxicity comparable with N516A alone. The introduction of these mutations reduced LF-mediated cleavage of MEK2 in cell-based assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…Acidic residues in domain III make on May 10, 2018 by guest http://iai.asm.org/ specific contact with the basic residues at the amino terminus of MAPKK (11). It has been presumed that LF-neutralizing antibody binds to domain I and thus directly inhibits the binding of LF to PA to neutralize LeTx (21,24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acidic residues in domain III make on May 10, 2018 by guest http://iai.asm.org/ specific contact with the basic residues at the amino terminus of MAPKK (11). It has been presumed that LF-neutralizing antibody binds to domain I and thus directly inhibits the binding of LF to PA to neutralize LeTx (21,24).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the structure-function relationship of LF, domain I of LF binds to PA, and domains II, III, and IV together create a long catalytic groove into which the amino terminus of MAPKK fits (11,20). Acidic residues in domain III make on May 10, 2018 by guest http://iai.asm.org/ specific contact with the basic residues at the amino terminus of MAPKK (11).…”
Section: Resultsmentioning
confidence: 99%
“…Lethal factor is a Zn 2+ -metalloprotease, which specifically cleaves the NH 2 -termini of MKK1, MKK2, MKK3, MKK4, MKK6, and MKK7, but not MKK5 (23)(24)(25). Cleavage results in loss of kinase function of MKKs (26). It has been shown that LeTx reverts the transformation of V12 H-ras-transformed NIH 3T3 cells in vitro and inhibits their growth and vascularization in vivo (27).…”
Section: Introductionmentioning
confidence: 99%
“…However, longer substrates can be cleaved more efficiently because of secondary interactions between LF and its substrate (10). We used phage display screening to determine the minimal length of substrate efficiently cleaved by LF and to identify substrate determinants responsible for optimal subsite occupancy in the LF-substrate interaction (19).…”
Section: Phage Display Library Screening and Substrate Selection-mentioning
confidence: 99%
“…Briefly, 10 11 purified phages in phosphate-buffered saline (1.7 mM NaH 2 PO 4 , 5.2 mM Na 2 HPO 4 , and 150 mM NaCl, pH 7.4) were applied to each well and incubated for 1 h at 25°C. The wells were then washed three times in phosphate-buffered saline, 0.05% Tween 20, blocked with 1% bovine serum albumin, and incubated with LF in test wells and without LF in control wells.…”
Section: Construction Of Phage Display Libraries and Selection Of Clonesmentioning
confidence: 99%